Functional state of the nigrostriatal system of Krushinsky – Molodkina rats during audiogenic seizure expression - N. A. Dorofeeva; L. S. Nikitina; D. V. Zosen; M. V. Glazova; E. V. Chernigovskaya (Вавиловский журнал генетики и селекции)
Neurochemical mechanisms of initiation and expression of epileptic seizures are poorly explored, and there are no published data that could demonstrate the functional state of the neuromediator systems at the initial state of seizure in the animals genetically prone to seizure. In the current work, we studied the role of extracellular signal-regulated kinase (ERK1/2) in the regulation of the nigrostriatal glutamate, GABA and dopamine neurons of Krushinsky – Molodkina rats at clonus-tonus and ataxia stages of audiogenic seizure. We demonstrated upregulation of ERK1/2 activity upon audio stimulation which was accompanied by increased activation of Synapsin I in the striatum and substantia nigra in comparison to intact Krushinsky – Molodkina rats. The observed exocytosis activation led to secretion of glutamate in the striatum and, as a result, to stimulation of seizures. However, at clonus-tonus stage in the striatum we revealed the changes that could participate in further inhibition of seizure activity, such as increased phosphorylation of tyrosine hydroxylase upon increased ERK1/2 activity followed by activation of dopamine release in the pars compacta of the substantia nigra. At the same time, enhanced D2 and increased D1 dopamine receptor contents were observed. These data revealed attenuation of direct (pro-seizure) and indirect (anti-seizure) pathways of the regulation of the substantia nigra GABA neurons. We demonstrated activation of GABA in the substantia nigra pars reticulate, which probably results in the inhibition of glutamate neurons of the thalamus and could be one of the mechanisms inhibiting seizure activity during ataxia.